Increase of sulfadiazine effect against Toxoplasma gondii by using watermelon or cantaloupe seeds - Chinchilla, M; Marin, R; Catarinella, G (Revista de Biología Tropical, 1990)
In an experimental model the anti-Toxoplasma effect of watermelon and cantaloupe seeds, together with sulfadiazine (Sd7.5 and Sd 15) given by oral route, were studied. Combination of any of these seeds with the drug was able to increase the survival time and cure sorne tachyzoite infected mice. The effect was produced either by peeled or complete seeds and more significant results were obtained when Sd7.5 and 103 tachyzoite inoculum was used in the model. Sorne Toxoplasma oocyst infected mice were cured with the seeds alone (75% for watermelon, 37,5 or 50% for cantaloupe. Body weight variations are independent of the treatment with Sd alone or in combination with watermeIon or cantaloupe seeds.